The ABCs of African American Women: Avoid, Be Respectful, and Comply - Cobbina-Dungy, Jennifer (Crime & delinquency, 2025)
The rise of the Black Lives Matter movement has led to a hyperfocus on perceptions and attitudes of Black individuals toward law enforcement. That focus, however, fails to acknowledge the strained relationship between police and Black individuals and how it impacts their experiences of safety and security. This study examines how 28 protesters perceive safety and security for Black people. Results indicated that many were concerned about Black people’s personal safety, as they felt some were unsafe traversing various areas while others described Black people as having to preemptively make efforts to navigate safety. Those concerns and strategies are symbolic of broad societal experiences.